Global Satellite Meteorological Observation (GSMO) Theory Volume 1 - Ilčev, Stojče Dimov (Springer International Publishing : Imprint: Springer, 2018)
This book presents the principal structure of space systems, functionality, media and applications for modern remote sensing, transmission systems, meteorological antennas, propagation meteorological observation and transferring weather data from satellite to the ground infrastructures and users. The book starts with a short background to the development of Radio and Space systems including overview, concepts and applications of satellite communications in function of transfer meteorological observation data and images. It goes on to discuss the fundamental principles of the space platforms and orbital parameters, lows of satellite motions, new types of launching systems, satellite orbits and geometric relations, spacecraft configuration, payload structure, type of onboard antenna systems, satellite orbits and components of satellite bus. The author also provides comprehensive coverage of baseband and transmission systems, fundamentals of atmospheric electromagnetic radiation, satellite meteorological parameters and instruments, and research and applications in antenna systems and propagation. This is a companion book of Global Satellite Meteorological Observation Applications (Springer).